Polarized Intestinal Cell Membrane‐on‐Chip for Bacterial Toxin Interaction Studies - Reece McCoy; Jeremy Treiber; George G. Malliaras; Alberto Salleo; Róisín M. Owens (Advanced NanoBiomed Research, 2025)
The virulence of a pathogen is tied to the successful interaction between the pathogen, or its toxins, and the host cell. Polarized epithelial cells, constituting highly specialized cell monolayers, possess apical and basolateral membrane regions with distinct functions and structural compositions. Preserving these intricacies in cell membrane‐on‐a‐chip platforms is important for retaining physiological relevance for investigating host–pathogen interactions. Consequently, a method for obtaining distinct populations of cell membrane vesicles representing the apical and basolateral membranes is presented here, in addition to the formation of their respective supported lipid bilayers (SLBs) on PEDOT:PSS conducting polymer electrodes. The apical localization of the A metalloprotease and disintegrin (ADAM10) receptor in Caco‐2 cells is shown to correlate with the increased response of the Staphylococcus aureus alpha hemolysin toxin on membrane‐on‐a‐chip platforms compared to the basolateral membrane model where the ADAM10 receptor is absent. The interaction between SLBs and the alpha hemolysin‐containing extracellular vesicles (EVs) secreted by S. aureus confirm the direct effect of toxin‐containing EVs on reducing the resistance of plasma membrane. This technique could find use in quantifying relative toxicity to the cell membrane, screening for cognate receptors and inhibitors, and probing toxin mechanism of action.